TOURISM TERMS IN ENGLISH AND UZBEK LINGUOCULTURAL ASPECTS - Muratova Dilorom Maxmudovna; Aslonova Nafosat Fakhridinovna (Journal of new century innovations, 2023)
Abstract: In the article, the linguistic and cultural terms specific to tourism are discussed aspects were considered on a scientific basis. Use of terms in situations and the method of use has been studied.